Efektifitas Pemberian Air Rebusan Cengkeh Terhadap Penurunan Kadar Asam Urat pada Lansia Penderita Gout Arthritis : The Effectiveness of Clove Boiled Water in Reducing Uric Acid Levels in Elderly Patients with Gout Arthritis - Nanik Rumdayati; Saiful Gunardi; Irma Herliana (MPI Press, 2026)
Introduction: Uric acid is the end product of purine metabolism that can accumulate and form monosodium urate crystals in the joints, causing inflammation and pain known as gout arthritis. In elderly individuals, gout arthritis is commonly characterized by elevated uric acid levels accompanied by joint pain, especially in the knees and ankles, stiffness, and discomfort during movement.Objective: This study aimed to determine the effectiveness of administering clove boiled water in reducing uric acid levels among elderly patients with gout arthritis.Method: This study used a pre-experimental design with a one group pre-test and post-test approach. The sample consisted of 30 respondents selected using purposive sampling technique. Data were collected through direct measurement of uric acid levels using the Easy Touch GCU Meter device before and after the administration of clove boiled water for seven days. Data analysis was conducted using univariate analysis to describe the distribution of uric acid levels and bivariate analysis using the Paired Sample T-Test to determine the effectiveness of the intervention.Result: The results showed a decrease in uric acid levels after the intervention. Statistical analysis using the Paired Sample T-Test demonstrated a significant effect of clove boiled water administration on reducing uric acid levels, with a p-value less than 0.05.Conclusion: Clove boiled water is effective in reducing uric acid levels in elderly patients with gout arthritis. It can be considered as a complementary non-pharmacological therapy alongside pharmacological treatment to help manage uric acid levels.